Tasting arterial blood: what do the carotid chemoreceptors sense? - Prabhakhar, Nanduri R.; Joyner, Michael J. (Frontiers in Physiology, 2015)
The carotid bodies are sensory organs that detect the chemical composition of the arterial blood. The carotid body sensory activity increases in response to arterial hypoxemia and the ensuing chemoreflex regulates vital homeostatic functions. Recent studies suggest that the carotid bodies might also sense arterial blood glucose and circulating insulin levels. This review focuses on how the carotid bodies sense O2, glucose, and insulin and some potential implications of these sensory functions on physiological regulation and in pathophysiological conditions. Emerging evidence suggests that carbon monoxide (CO)-regulated hydrogen sulfide (H2S), stemming from hypoxia, depolarizes type I cells by inhibiting certain K+ channels, facilitates voltage-gated Ca2+ influx leading to sensory excitation of the carotid body. Elevated CO and decreased H2S renders the carotid bodies insensitive to hypoxia resulting in attenuated ventilatory adaptations to high altitude hypoxia, whereas reduced CO and high H2S result in hypersensitivity of the carotid bodies to hypoxia and hypertension. Acute hypoglycemia augments the carotid body responses to hypoxia but that a prolonged lack of glucose in the carotid bodies can lead to a failure to sense hypoxia. Emerging evidence also indicates that carotid bodies might sense insulin directly independent of its effect on glucose, linking the carotid bodies to the pathophysiological consequences of the metabolic syndrome. How glucose and insulin interact with the CO-H2S signaling is an area of ongoing study.